1981
DOI: 10.1093/nar/9.4.971
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence of the constant gene region of the mouse immunoglobulin kappa chain

Abstract: The constant (C; ref.3) gene segment of the immunoglobulin kappa light chain and about 1 kb upstream as well as downstream of the segment have been sequenced. The sequences of the C gene segment itself and parts of the upstream region were determined both in liver and in myeloma T DNA clones derived from the same mouse inbred strain. The sequences were identical, i.e. no somatic mutations were detected. Two sites in the region not coding for protein are discussed as possible targets of aberrant variable (V) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The predicted amino acid sequence of D23 L chain differed from the complete protein sequence of anti-phosphocholine mAb MCPC603 (31) by 15 amino acids (86% homology), whereas identity was found in the first 38 amino acids of another anti-phosphocholine mAb (HPCG15) (14), and only 1 difference was observed in the 48-amino acid partial protein sequences of anti-arsonate mAb 45.165 (30) ( Table 2). The CK and complete 3' untranslated regions (data not shown) of E7 and D23 were identical to the germ-line BALB/c C1 (33). DISCUSSION We report here the nucleotide sequence of two preimmune natural polyreactive autoantibodies, E7 and D23, which react with antigens such as DNA, myosin, actin, tubulin, spectrin, and TNP.…”
Section: E S G V P D R F T 0 S C S 0 T D F T L T I S S V Q a E D Lmentioning
confidence: 55%
“…The predicted amino acid sequence of D23 L chain differed from the complete protein sequence of anti-phosphocholine mAb MCPC603 (31) by 15 amino acids (86% homology), whereas identity was found in the first 38 amino acids of another anti-phosphocholine mAb (HPCG15) (14), and only 1 difference was observed in the 48-amino acid partial protein sequences of anti-arsonate mAb 45.165 (30) ( Table 2). The CK and complete 3' untranslated regions (data not shown) of E7 and D23 were identical to the germ-line BALB/c C1 (33). DISCUSSION We report here the nucleotide sequence of two preimmune natural polyreactive autoantibodies, E7 and D23, which react with antigens such as DNA, myosin, actin, tubulin, spectrin, and TNP.…”
Section: E S G V P D R F T 0 S C S 0 T D F T L T I S S V Q a E D Lmentioning
confidence: 55%
“…To evaluate possible mechanisms, information on the distribution of somatic mutations is undoubtedly required (5,(16)(17)(18)(19). Both murine and human immunoglobulin gene sequences show a lack of somatic mutation in the constant (C) region exons of H and K chains (5,17,20,21). However, Cleary et al (22) reported the occurrence of somatic mutation in the human CA exon.…”
mentioning
confidence: 99%
“…Chicken 3-globin 15 11 Human IgG K chain constant 16 12 Mouse IgG K chain constant 17 13 Mouse IgG1 constant 18 14 Mouse IgG K chain variable 19 15 Mouse IgG2 variable 20 16 Human preproinsulin 21, 22 17 Rat preproinsulin 23 18 Chicken preproinsulin 24 …”
mentioning
confidence: 99%
“…The other 9 globins are well-represented by a single Markov chain of order 1 ( Table 3 (rows [14][15][16][17]. In most cases, they are less similar than pairs of noncoding sequences in Table 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation